Are Intercultural Situations a Problem? A Strenght and Self Readiness Provisioning in Penang, Malaysia - Soelton, Mochamad; Karyatun, Subur; Harwani, Yuli; Asih, Daru; Ali, Anees Janee; Yuliantini, Tine; Rahmad, Khozaeni Bin (Faculty of Economics, Universitas Sriwijaya, 2024)
Population growth is very high and is not balanced with the availability of jobs, resulting in uncontrolled poverty. Until now, unemployment is still a crucial problem for the Indonesian government. With minimal levels of education and skills, these job seekers have to compete with each other. This condition ultimately became the trigger for mass labor mobilization between countries carried out by the government. To alleviate poverty, the government implemented a program to place Indonesian Migrant Workers (TKI) abroad. The government's role in this program is focused on aspects of training, protection and providing various conveniences to related parties, especially TKI and Indonesian Migrant Worker Placement Services Companies (PJTKI). The aim of this community service is to empower informal workers and learning sector facilitators by strengthening the individual potential of the Indonesian Community Association (PERMAI) Pulai Pinang with a differentiated learning approach that favors the informal sector workers themselves, as well as an effort to adapt the adjustment process to the work community which exists. In Malaysia, adjustment includes interest, strengthening one's potential, and individual readiness to achieve increased productivity results. The solution is to strengthen individuals and/or facilitators in differentiated learning with a learning pattern approach that focuses on increasing productivity levels, through several stages. Stage 1: Map and collect data on initial partner conditions; Stage 2, Socialization through discussions with partners regarding implementation preparations, implementation time, members involved and service topics at Partners; Stage 3: Training and empowerment of differentiated learning and learning pattern approaches that focus on increasing productivity levels; Stage 4: Assistance in implementing learning approaches to learning patterns that favor increasing productivity levels; Stage 5: monitor and evaluate all partner activities; Stage 6: Follow-up on program implementation.